2002
DOI: 10.1097/00007632-200207150-00015
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Thoracic Pedicle Screws in Patients with and Without Coronal Plane Spinal Deformities

Abstract: The overall percentage of acceptably positioned screws was 98% in patients with coronal plane spinal deformities and 99% in patients without coronal plane spinal deformities. In patients with coronal plane spinal deformities, penetration of the pedicle wall and the anterior vertebral cortex was increased at T9-T12 and overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 37 publications
6
81
1
Order By: Relevance
“…Figure 1 a-c provides examples of typical breaches encountered. This is similar to what others have reported [1].…”
Section: Evaluation Of Pedicle Breachsupporting
confidence: 93%
See 2 more Smart Citations
“…Figure 1 a-c provides examples of typical breaches encountered. This is similar to what others have reported [1].…”
Section: Evaluation Of Pedicle Breachsupporting
confidence: 93%
“…However, the vast majority of these were evaluated with plain X-rays. Belmont et al [1], using postoperative CT, reported a breach rate of 58% in patients with coronal plane deformity. A few other studies report on breach rates for thoracic screw placement in deformity utilizing postoperative CT [9,14,20,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure of pedicle screw insertion is complicated and has a steep learning curve. Several institutions have reported the complication rates for pedicle screw surgery from 3% to 55%, with a rate of malpositioning from 1.5% to 6.7% [5][6][7][8][9][10][11][12][13] and breach rates from 1.5% to 58% [12,14,15,16]. However, these results were not comprehensive due to a lack of reports from small medical centers and newer surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…9,[10][11][12] Many of the differences in the literature depend on the study methodology used to determine the perforation. Perforations can further lead to complications such as dural tear, 12 nerve root injuries, 12 paraplegia, [12][13][14][15] or vascular injury.…”
Section: Introductionmentioning
confidence: 99%